ANALISIS DAN SIMULASI NUMERIS DEFORMASI RAFT FOOTING DI ATAS TANAH LUNAK DENGAN MENGGUNAKAN PEMODELAN TANAH MOHR COULOMB (Studi kasus: Bangunan Fakultas Hukum Universitas Sultan Agung Semarang) - Irdhiani, Irdhiani (MEKTEK, 2008)
The main problem in designing construction structure on soft soil is a considerable large deformation, therefore in this research light material is used that is styrofoam concrete to replace landfill in raft footing so the deformation can be reduced. The percentage styrofoam used in concrete miixture are 40%, 60%, 80% dan 100%, then the deformation form caused by construction weight is analysed using Plaxis sofware version 7.0 with soil model Mohr-Coulomb at three soil water surface condition, they are in very deep water surface, in foundation base and on soil surface. The research result shows that the large the total construction weight, the larger vertical and horisontal movements happened. For styrofoam concrete with the percentage of styrofoam 100% the vertical movement is the opposite direction with other material-fills, because the total weight of construction is lesser than excavated soil weight at 2,45 meter deep.